2021
DOI: 10.1007/s43452-021-00234-2
|View full text |Cite
|
Sign up to set email alerts
|

The performance of ultra-lightweight foamed concrete incorporating nanosilica

Abstract: This paper aims to investigate the feasibility of the incorporation of nanosilica (NS) in ultra-lightweight foamed concrete (ULFC), with an oven-dry density of 350 kg/m3, in regard to its fresh and hardened characteristics. The performance of various dosages of NS, up to 10 wt.-%, were examined. In addition, fly ash and silica fume were used as cement replacing materials, to compare their influence on the properties of foamed concrete. Mechanical and physical properties, drying shrinkage and the sorption of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 50 publications
(81 reference statements)
0
11
0
Order By: Relevance
“…Results of experimental studies on the influence of the volumetric content of fiber-reinforced concrete and the method of its distribution in the preparation of a fiber-concrete mixture on the physical-mechanical and deformative characteristics of LFRC on a combined aggregate. Figures [8][9][10][11][12] show that the largest increase in compressive and tensile strength in bending, prismatic strength, axial tensile strength, elastic modulus as well as the smallest ultimate deformations during the axial compression and tension of fiber-reinforced concrete are observed with the following composition and technological parameters: the volumetric content of basalt fiber is 2%, the method of fiber distribution is 2t (preliminary mixing of cement, sand, crushed stone + mixing with fiber + mixing with water). This amount of basalt fiber is also confirmed by previous studies [35] and is comparable to the results of similar studies by other authors [2,5,11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of experimental studies on the influence of the volumetric content of fiber-reinforced concrete and the method of its distribution in the preparation of a fiber-concrete mixture on the physical-mechanical and deformative characteristics of LFRC on a combined aggregate. Figures [8][9][10][11][12] show that the largest increase in compressive and tensile strength in bending, prismatic strength, axial tensile strength, elastic modulus as well as the smallest ultimate deformations during the axial compression and tension of fiber-reinforced concrete are observed with the following composition and technological parameters: the volumetric content of basalt fiber is 2%, the method of fiber distribution is 2t (preliminary mixing of cement, sand, crushed stone + mixing with fiber + mixing with water). This amount of basalt fiber is also confirmed by previous studies [35] and is comparable to the results of similar studies by other authors [2,5,11].…”
Section: Resultsmentioning
confidence: 99%
“…The possibility of using a mixture of cement, fly ash, ground granulated blast-furnace slag, and river sand to produce pre-foamed ultralight composite material (PULC) was investigated in [12]. It was shown that replacing 20% cement with slag resulted in the highest compressive strength as well as the lowest the water absorption value of the PULC samples.…”
mentioning
confidence: 99%
“…An image found during a moment was found in a generic vessel at 28. In general, it was found to be more effective than other conventional materials in improving the stability of a mixture [8]. Mixtures manufactured to prepare aggregate foam have been tested for thermal, mechanical, absorbent, and high temperature resistance [9].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the strength, the concrete divided into 3 categories namely low strength concrete where fc' < 20 MPa, medium strength concrete where fc' = 21 MPa -40 MPa, and high strength concrete where fc' > 41 Mpa [2], [3], [4]. Meanwhile, [5] categorized the concrete into low-strength concretes in range of [0.7 MPa-2.0 MPa], moderate-strength concretes in range of [7][8][9][10][11][12][13][14] MPa] and structural concretes in range of . Based on the density, concrete is divided into 3 categorizes namely lightweight concrete with a unit weight of < 1,900 kg/m³, normal weight concrete with a unit weight of 2,200 kg/m³ -2,500 kg/m³ and heavy weight concrete with a unit weight of > 2,500 kg/m³ [1].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the use of foam aagentswill affect the absorption rate of the concrete [9]. Foam agent is a chemical material which is frequently used in the manufacturing of lightweight foam concrete [10], [11], [12]. Foam agents can be classified into 3 types, namely polymer foam agent, protein foam agent and surface-active agent [13].…”
Section: Introductionmentioning
confidence: 99%